Putting Yourself in the Skin of In- or Out-Group Members: No Effect of Implicit Biases on Egocentric Mental Transformation - Saetta, Gianluca; Brugger, Peter; Schrohe, Hannah; Lenggenhager, Bigna (Frontiers in Psychology, 2019)
Previous studies suggest that visual encoding of ethnicity of ingroup/outgroup members might influence empathy and sensorimotor sharing. Here, we investigated whether mental perspective taking, presumably a precursor of empathy, is also influenced by ingroup/outgroup perception and the implicit attitudes towards it. We used an embodied egocentric visual-perspective taking task, the full body rotation task (FBR), in which participants were asked to mentally rotate themselves into the position of dark- or light-skinned bodies. FBR was contrasted to a pure sensorimotor task, the hand laterality task (HLT), in which participants were asked to mentally rotate their hand to the posture of seen light- or dark-skinned hands, which does not require mental simulation of another person’s perspective. We expected the FBR but not the HLT to be influenced by the skin color of the stimuli and by the individual implicit biases towards outgroup members. Contrary to this hypothesis, we found that neither skin color nor implicit biases modulated reaction times (RTs) in either task. The data thus suggest that unlike other empathy tasks, skin color does not influence visuo-spatial perspective taking.